Freeze-dried glucose block and production process thereof
The composite lyophilization improver forms a dense three-dimensional mesh hole in the lyophilization body, which solves the problems of long lyophilization time and high energy consumption in traditional lyophilization technology, and achieves efficient and low-cost lyophilization preparation, improving the product pass rate.
Patent Information
- Application Number
- CN202510769174.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-07-18
- Estimated Expiration
- 2045-06-10
AI Technical Summary
Traditional vacuum freeze-drying technology has problems such as long freeze-drying time, high energy consumption and high product cracking rate, making it difficult to achieve efficient and low-cost freeze-drying preparation.
Using a composite lyophilization improver, microbubble gas is introduced through the gas induction agent, combined with the nanocellulose three-dimensional skeleton and ultrasonic vibration, a dense penetrating three-dimensional mesh channel is formed in the lyophilized body, which synergistically accelerates the sublimation of water molecules, reduces the lyophilization temperature and reduces the lyophilization time.
Significantly reduce freeze-drying time, save energy consumption, improve product qualification rate, reduce production costs, and have wide application prospects.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of food preparation, and particularly to a freeze-dried glucose block and its production process. Background Art
[0002] Vacuum freeze-drying technology, namely vacuum lyophilization technology, is an advanced drying process that removes moisture from materials through low-temperature freezing and vacuum sublimation. Its core principle lies in utilizing the triple-phase change characteristics of water to directly achieve sublimation dehydration between the solid state (ice) and the gaseous state (vapor).
[0003] Traditional vacuum freeze-drying technology has the following significant defects: (1) Simply relying on low-temperature vacuum dehydration easily leads to the densification of the material structure, blocking the diffusion channels of water molecules and requiring an extended drying time (usually 15 - 30 hours); (2) To maintain ice crystal sublimation, a high vacuum of 0.1 - 1 mbar needs to be maintained, and the energy consumption accounts for more than 60% of the total cost; (3) The shrinkage of the organizational structure easily causes product cracking (the unqualified rate is about 8 - 12%).
[0004] Therefore, there is an urgent need for a production process that can significantly reduce the temperature during freeze-drying, remarkably shorten the freeze-drying time, greatly save energy consumption, achieve the freeze-dried preparation of products without a high vacuum degree, improve the product qualification rate, and significantly reduce the production cost.
[0005] The present invention breakthroughly adopts a composite freeze-drying improver multi-component synergistic system: introducing microbubble gas through an air-entraining agent, and the three-dimensional nanocellulose framework and pre-sublimation ultrasonic vibration in the freeze-dried body synergistically guide the diffusion and escape of the microbubble gas. After the gas diffuses, a dense and through three-dimensional network pore structure with an average pore diameter of 50 - 100 μm is formed in the freeze-dried body; due to the special preparation raw materials of the present invention, the pores are unsupported and prone to collapse, and then the structural stability of the pores is effectively maintained by inhibiting the glass transition of maltodextrin. Through the synergistic action of the air-entraining agent, nanocellulose, ultrasonic vibration, and maltodextrin, the formed dense and through three-dimensional network pore structure significantly accelerates the sublimation and overflow time of water molecules, greatly reduces the temperature during freeze-drying and significantly shortens the freeze-drying time, greatly saves energy consumption, can achieve the freeze-dried preparation of glucose block products without a high vacuum degree, improves the product qualification rate, and significantly reduces the production cost through the composite freeze-drying improver. Summary of the Invention
[0006] The object of the present invention is to overcome the shortcomings of the prior art and provide a freeze-dried glucose block and its production process, which mainly consists of the following raw materials: glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid and a composite freeze-drying improver. The composite freeze-drying improver is a mixture of an air-entraining agent, nanocellulose and maltodextrin; the freeze-dried glucose block introduces gas through the air-entraining agent in the composite freeze-drying improver, and through the nanocellulose, maltodextrin and the introduced gas in the composite freeze-drying improver, a porous network structure is formed in the freeze-dried body in cooperation with ultrasonic vibration during the freeze-drying sublimation stage, thereby greatly reducing the temperature during the freeze-drying process and significantly reducing the freeze-drying time, greatly saving energy consumption, and realizing the freeze-drying preparation of the product without a high vacuum degree, improving the product qualification rate, and through the composite freeze-drying improver, the production cost can be greatly reduced, and it has outstanding application and promotion prospects.
[0007] To achieve the above technical effects, the following technical solutions are adopted: A production process of a freeze-dried glucose block, comprising the following steps: Step S1: Dissolve raw materials and entrain gas The raw materials qualified by quality inspection are weighed according to the formula amount. After the glucose is crushed and sieved, the weighed glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid and the composite freeze-drying improver are added to a blender, stirring is started and gas is introduced into the mixed solution to obtain a glucose foaming suspension solution; the composite freeze-drying improver is dissolved in hot water and then added to the blender; Step S2: Filling and quick-freezing The glucose foaming suspension solution obtained in Step S1 is filled into a mold, and the glucose foaming suspension solution filled into the mold enters a liquid nitrogen quick-freezing tunnel through a conveyor belt for quick-freezing to obtain a quick-frozen glucose block; Step S3: Demolding and freezing The quick-frozen glucose block obtained in Step S2 is demolded, and after demolding, it is transferred to a freeze-drying tray and quickly enters a freezing warehouse for freezing to obtain a frozen glucose block; Step S4: Freeze-dry with ultrasonic vibration in a freeze-dryer and then discharge The frozen glucose block obtained in Step S3 quickly enters a freeze-dryer and is placed on the ultrasonic vibration table of the freeze-dryer. The vacuum is pumped at a low temperature. When the vacuum degree reaches the preset value, heating is started. When the temperature of the heating plate reaches 5 - 10 °C, ultrasonic vibration is started. After reaching the preset ultrasonic vibration time, ultrasonic vibration is turned off and sublimation drying continues. When the temperature of the glucose block material coincides with the preset temperature of the heating plate, the temperature is reduced and drying continues and then discharged; vacuum freeze-drying is completed to obtain the freeze-dried glucose block; through discharging, sorting, metal detection, bagging and sealing, and after passing the inspection, the finished product is warehoused; The composite freeze-drying improver is a mixture of an air-entraining agent, nanocellulose and maltodextrin; The air-entraining agent is sucrose fatty acid ester SE-15; The diameter of the nano-cellulose is 20-30 nm, the length is 1200-2600 nm, the degree of polymerization is 200-660, and the crystallinity is 60-75.
[0008] Furthermore, in the step S1, the mass fraction ratio of glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid and the composite freeze-drying improver is 42.5-47.5: 40.5-45.0: 6.0-8.5: 1.0-2.0: 0.35-0.50: 0.2-0.3: 3.5-5.5; the gas is nitrogen, carbon dioxide or air.
[0009] Furthermore, in the composite freeze-drying improver in the step S1, the mass fraction ratio of the air-entraining agent sucrose fatty acid ester SE-15, nano-cellulose and maltodextrin is 0.5-0.75: 30.0-50.0: 2.0-4.0.
[0010] Furthermore, in the step S1, the stirring temperature is 2-5 °C; the stirring speed is 600-1000 r / min; the stirring time is 3-5 min.
[0011] Furthermore, in the step S2, the speed of the conveyor belt entering the liquid nitrogen quick-freezing tunnel is 250~300 kg / h, the temperature is -50 °C, and the time to exit the tunnel is 10~20 min.
[0012] Furthermore, in the step S3, the freezing temperature is less than -35 °C, and the freezing time is greater than 8 h.
[0013] Furthermore, in the step S4, the vacuum degree reaches 30-100 Pa within 1 h; the preset temperature of the heating plate is 50-70 °C; the heating rate of the heating plate is 0.7-5 °C / min.
[0014] Furthermore, in the step S4, the ultrasonic vibration frequency is 10-20 kHz; the ultrasonic amplitude is 10-20 μm; the preset ultrasonic vibration time is 20-40 min.
[0015] Furthermore, in the step S4, after the temperature of the glucose block material coincides with the preset temperature of the heating plate, continue drying for 1-2 h and then discharge, and the vacuum freeze-drying time is 6-12 h.
[0016] A freeze-dried glucose block is prepared by the preparation method of any one of the above.
[0017] The beneficial effects of the present invention are: The present invention discloses a freeze-dried glucose block and its production process, which mainly consists of the following raw materials: glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid, and a composite freeze-drying improver. The composite freeze-drying improver is an air-entraining agent, a mixture of nanocellulose and maltodextrin. The present invention breakthroughly adopts a composite freeze-drying improver multi-component synergistic system: microbubble gas is introduced through the air-entraining agent, and the three-dimensional skeleton of nanocellulose and ultrasonic vibration in the early sublimation stage in the freeze-dried body synergistically guide the diffusion and escape of the microbubble gas. After the gas diffuses, a dense and through three-dimensional network pore structure with an average pore diameter of 50-100 μm is formed in the freeze-dried body. Due to the special preparation raw materials of the present invention, the pores are unsupported and prone to collapse. Then, the glass transition of maltodextrin is inhibited to effectively maintain the structural stability of the pores and prevent collapse. Through the synergistic action of the air-entraining agent, nanocellulose, ultrasonic vibration, and maltodextrin, the formed dense and through three-dimensional network pore structure significantly accelerates the sublimation and overflow time of water molecules, greatly reduces the temperature during the freeze-drying process, and significantly reduces the freeze-drying time, greatly saving energy consumption. The freeze-dried preparation of glucose block products can be realized without a high vacuum degree, improving the product qualification rate, and significantly reducing the production cost through the composite freeze-drying improver. It has outstanding application and promotion prospects. Detailed Embodiments
[0018] In order to make the objectives, technical solutions and advantages of the present invention clearer, the following further describes the present invention in detail with reference to embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, but not to limit the present invention.
[0019] It should be noted that the following detailed descriptions are all exemplary and are intended to provide further explanations of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present invention belongs.
[0020] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, and / or combinations thereof.
[0021] Example 1: This example relates to a freeze-dried glucose block and its production process: Step S1: Dissolve the raw materials and introduce gas The raw materials that pass the quality inspection are weighed according to the formula amount. After crushing and sieving glucose, the weighed glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid, and compound freeze-drying improver are added to a blender. The mass fraction ratio of glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid, and compound freeze-drying improver is 42.5 parts: 40.5 parts: 6.0 parts: 2.0 parts: 0.35 parts: 0.2 parts: 3.5 parts. Start stirring and introduce gas (nitrogen) into the mixed solution. The stirring temperature is 2 °C, the stirring speed is 600 r / min, and the stirring time is 3 min to obtain a glucose foaming suspension solution. The compound freeze-drying improver is dissolved in hot water and then added to the blender. The compound freeze-drying improver is a mixture of an air-entraining agent, sucrose fatty acid ester SE-15, nanocellulose (with a diameter of 20 - 30 nm, a length of 1200 - 2600 nm, a degree of polymerization of 200 - 660, and a crystallinity of 60 - 75), and maltodextrin. Among them, the mass fraction ratio of sucrose fatty acid ester SE-15, nanocellulose, and maltodextrin is 0.5 parts: 30.0 parts: 2.0 parts.
[0022] Step S2: Filling and quick-freezing The glucose foaming suspension solution obtained in Step S1 is filled into molds, with a weight of about 11 g / granule and a filling speed of 380 granules / min. The glucose foaming suspension solution filled into the molds enters a liquid nitrogen quick-freezing tunnel through a conveyor belt. The conveyor belt enters the liquid nitrogen quick-freezing tunnel at a speed of 250 kg / h, at a temperature of -50 °C, and exits the tunnel after 10 min for quick-freezing to obtain quick-frozen glucose blocks. Step S3: Demolding and freezing Demold the quick-frozen glucose blocks obtained in Step S2. After demolding, transfer them to a freeze-drying tray. The demolding environment temperature is room temperature, and demolding is carried out on a stainless-steel operating table. Each freeze-drying tray contains 648 granules / tray, and 68 trays / trailer. After the trailer is full, quickly enter the freezing storage for freezing. The freezing temperature is less than -35 °C, and the freezing time is more than 8 h to obtain frozen glucose blocks. Step S4: Freeze-dry in a freeze-dryer with ultrasonic vibration and then discharge Quickly transfer the frozen glucose blocks obtained in step S3 into a freeze dryer and place them on the ultrasonic vibration table of the freeze dryer. Conduct low-temperature vacuum pumping, with the preset vacuum value reaching 30 Pa within 1 h. When the vacuum reaches the preset value, turn on the heating. The preset temperature of the heating plate is 50 °C, and the heating rate of the heating plate is 2.2 °C / min. When the temperature of the heating plate reaches 5 °C, turn on the ultrasonic vibration, with the ultrasonic vibration frequency being 10 kHz, the ultrasonic amplitude being 10 μm, and the preset ultrasonic vibration time being 20 min. After reaching the preset ultrasonic vibration time, turn off the ultrasonic vibration and continue sublimation drying. When the temperature of the glucose block material coincides with the preset temperature of the heating plate, lower the temperature and continue drying for 1 h before discharging. Complete vacuum freeze-drying to obtain the freeze-dried glucose blocks. After discharging, sorting, metal detection, bagging and sealing, and passing the inspection, the finished products are warehoused. Perform quality index detection on the freeze-dried glucose blocks prepared in Example 1 to verify whether they meet the internal control quality indicators, and summarize them in Table 1: Table 1 Qualified indicators and actual test results of the freeze-dried glucose blocks in Example 1
[0023] According to the experimental results in Table 1 above, the internal control quality indicators can be achieved. According to the production process in Example 1, the drying time is 7.4 h (starting from the time when the freeze dryer starts vacuum pumping until the time of discharging).
[0024] Example 2: This example relates to a freeze-dried glucose block and its production process: Step S1: Dissolve the raw materials and introduce gas Weigh the raw materials that have passed the quality inspection according to the formula amount. After crushing and sieving the glucose, add the weighed glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid, and composite freeze-drying improver into a blender. The mass fraction ratio of glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid, and composite freeze-drying improver is 47.5 parts: 45.0 parts: 8.5 parts: 1.0 part: 0.50 part: 0.3 part: 5.5 parts. Turn on the stirring and introduce gas (air) into the mixed solution. The stirring temperature is 5 °C, the stirring speed is 1000 r / min, and the stirring time is 5 min to obtain a glucose foaming suspension solution. The composite freeze-drying improver is dissolved in hot water and then added to the blender. The composite freeze-drying improver is a mixture of the air-entraining agent sucrose fatty acid ester SE-15, nanocellulose (with a diameter of 20 - 30 nm, a length of 1200 - 2600 nm, a degree of polymerization of 200 - 660, and a crystallinity of 60 - 75), and maltodextrin. Among them, the mass fraction ratio of sucrose fatty acid ester SE-15, nanocellulose, and maltodextrin is 0.75 part: 50.0 parts: 4.0 parts.
[0025] Step S2: Filling and Quick Freezing The glucose foaming suspension solution obtained in Step S1 is filled into a mold, with a weight of about 11 g per pellet and a filling speed of 380 pellets / min. The glucose foaming suspension solution filled into the mold enters the liquid nitrogen quick-freezing tunnel through a conveyor belt. The speed of the conveyor belt entering the liquid nitrogen quick-freezing tunnel is 300 kg / h, the temperature is -50°C, and it exits the tunnel after 20 minutes for quick freezing to obtain quick-frozen glucose blocks; Step S3: Demolding and Freezing The quick-frozen glucose blocks obtained in Step S2 are demolded. After demolding, they are transferred to a freeze-drying tray. The demolding environment temperature is normal temperature, and demolding is carried out on a stainless-steel operating table. Each freeze-drying tray contains 648 pellets / tray, and 68 trays / trailer. After the trailer is full, it quickly enters the freezing warehouse for freezing. The freezing temperature is less than -35°C, and the freezing time is more than 8 hours to obtain frozen glucose blocks; Step S4: Freeze-drying with ultrasonic vibration in a freeze-dryer and then discharging The frozen glucose blocks obtained in Step S3 quickly enter the freeze-dryer and are placed on the ultrasonic vibration table of the freeze-dryer. It is evacuated at low temperature, and the preset value of the vacuum degree is to reach 100 Pa within 1 hour. When the vacuum degree reaches the preset value, heating is started. The preset temperature of the heating plate is 70°C, and the heating rate of the heating plate is 1.4°C / min; when the temperature of the heating plate reaches 10°C, ultrasonic vibration is started, the ultrasonic vibration frequency is 20 kHz; the ultrasonic amplitude is 20 μm; the preset time of ultrasonic vibration is 40 minutes; after reaching the preset time of ultrasonic vibration, ultrasonic vibration is turned off and sublimation drying is continued. When the temperature of the glucose block material coincides with the preset temperature of the heating plate, the temperature is reduced, and drying is continued for 2 hours and then discharged; vacuum freeze-drying is completed to obtain the freeze-dried glucose blocks; through discharging, sorting, metal detection, bagging and sealing, and passing the inspection, the finished products are warehoused; The quality indicators of the freeze-dried glucose blocks prepared in Example 2 are detected to verify whether they meet the internal control quality indicators, and the results are summarized in Table 2: Table 2 Qualified indicators and actual test results of the freeze-dried glucose blocks in Example 2
[0026] According to the experimental results in Table 2 above, the internal control quality indicators can be achieved. According to the production process in Example 2, the drying time is 7.1 h (starting from when the freeze-dryer starts to evacuate and ending when discharging).
[0027] Example 3: This example relates to a freeze-dried glucose block and its production process: Step S1: Dissolving raw materials and introducing gas The raw materials that pass the quality inspection are weighed according to the formula amount. After crushing and sieving glucose, the weighed glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid, and compound freeze-drying improver are added to a blender. The mass fraction ratio of glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid, and compound freeze-drying improver is 45.0 parts: 42.5 parts: 7.5 parts: 1.5 parts: 0.40 parts: 0.25 parts: 4.5 parts; start stirring and introduce gas (carbon dioxide) into the mixed solution. The stirring temperature is 3°C; the stirring speed is 800 r / min; the stirring time is 4 min to obtain a glucose foaming suspension solution; the compound freeze-drying improver is dissolved in hot water and then added to the blender; The compound freeze-drying improver is a mixture of an air-entraining agent, sucrose fatty acid ester SE-15, nanocellulose (with a diameter of 20 - 30 nm, a length of 1200 - 2600 nm, a degree of polymerization of 200 - 660, and a crystallinity of 60 - 75), and maltodextrin; among them, the mass fraction ratio of sucrose fatty acid ester SE-15, nanocellulose, and maltodextrin is 0.65 parts: 40.0 parts: 3.0 parts.
[0028] Step S2: Filling and quick-freezing The glucose foaming suspension solution obtained in Step S1 is filled into molds, with a weight of about 11 g / granule and a filling speed of 380 granules / min. The glucose foaming suspension solution filled into the molds enters a liquid nitrogen quick-freezing tunnel through a conveyor belt. The conveyor belt enters the liquid nitrogen quick-freezing tunnel at a speed of 280 kg / h, at a temperature of -50°C, and exits the tunnel after 15 min for quick-freezing to obtain quick-frozen glucose blocks; Step S3: Demolding and freezing Demold the quick-frozen glucose blocks obtained in Step S2. After demolding, transfer them to a freeze-drying tray. The demolding environment temperature is normal temperature, and demolding is carried out on a stainless-steel workbench. Each freeze-drying tray contains 648 granules / tray, and 68 trays / trailer. After the trailer is full, quickly enter the freezing warehouse for freezing. The freezing temperature is less than -35°C, and the freezing time is more than 8 h to obtain frozen glucose blocks; Step S4: Carry out freeze-drying in a freeze-dryer with ultrasonic vibration and then discharge the material Quickly transfer the frozen glucose blocks obtained in step S3 into a freeze dryer and place them on the ultrasonic vibration table of the freeze dryer. Evacuate at low temperature, with the preset vacuum value reaching 80 Pa within 1 h. When the vacuum reaches the preset value, turn on the heating. The preset temperature of the heating plate is 60 °C, and the heating rate of the heating plate is 1.7 °C / min. When the temperature of the heating plate reaches 5 °C, turn on the ultrasonic vibration. The ultrasonic vibration frequency is 15 kHz; the ultrasonic amplitude is 15 μm; the preset ultrasonic vibration time is 30 min. After reaching the preset ultrasonic vibration time, turn off the ultrasonic vibration and continue sublimation drying. When the temperature of the glucose block material coincides with the preset temperature of the heating plate, lower the temperature and continue drying for 1.5 h before discharging; complete vacuum freeze-drying to obtain the freeze-dried glucose blocks; after discharging, sorting, metal detection, bagging and sealing, and passing the inspection, the finished products are warehoused; Perform quality index detection on the freeze-dried glucose blocks prepared in Example 3 to verify whether they meet the internal control quality indexes, and the statistics are shown in Table 3: Table 3 Qualified indexes and actual test results of freeze-dried glucose blocks in Example 3
[0029] According to the experimental results in Table 3 above, the internal control quality indexes can be achieved. According to the production process in Example 3, the drying time is 6.9 h (starting from the time when the freeze dryer starts to evacuate until the time of discharging).
[0030] Comparative Example 1: Based on Example 3, only the composite freeze-drying improver is not added, and ultrasonic vibration is not provided during the sublimation stage. The others are the same as in Example 3: Perform quality index detection on the freeze-dried glucose blocks prepared in Comparative Example 1 to verify whether they meet the internal control quality indexes, and the statistics are shown in Table 4: Table 4 Qualified indexes and actual test results of freeze-dried glucose blocks in Comparative Example 1
[0031] According to the experimental results in Table 4 above, the internal control quality indexes can be achieved. According to the production process in Comparative Example 1, the drying time is 23.5 h (starting from the time when the freeze dryer starts to evacuate until the time of discharging).
[0032] Comparative Example 2: Based on Example 3, only the formula of the composite freeze-drying improver is as follows: The freeze-drying improver is the air-entraining agent sucrose fatty acid ester SE-15; among them, sucrose fatty acid ester SE-15 is added according to the actual addition amount of sucrose fatty acid ester SE-15 in Example 3, that is, the proportional addition amount under the original composite formula, and ultrasonic vibration is not provided during the sublimation stage. The others are the same as in Example 3: The quality indicators of the freeze-dried glucose blocks prepared in Comparative Example 2 were detected to verify whether they meet the internal control quality indicators, and the results are summarized in Table 5: Table 5 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 2
[0033] According to the experimental results in Table 5 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 2, the drying time is 20.4 h (starting from the time when the freeze-dryer starts to evacuate and ending when the material is discharged).
[0034] Comparative Example 3: Based on Example 3, the formula of the composite freeze-drying improver is as follows: The composite freeze-drying improver is nanocellulose (with a diameter of 20 - 30 nm, a length of 1200 - 2600 nm, a degree of polymerization of 200 - 660, and a crystallinity of 60 - 75); among them, the nanocellulose is added according to the addition amount of the composite improver in Example 3, that is, the total component addition amount under the original composite formula, and no ultrasonic vibration is provided during the sublimation stage, and the others are the same as in Example 3: The quality indicators of the freeze-dried glucose blocks prepared in Comparative Example 3 were detected to verify whether they meet the internal control quality indicators, and the results are summarized in Table 6: Table 6 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 3
[0035] According to the experimental results in Table 6 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 3, the drying time is 20.2 h (starting from the time when the freeze-dryer starts to evacuate and ending when the material is discharged).
[0036] Comparative Example 4: Based on Example 3, the formula of the composite freeze-drying improver is as follows: The composite freeze-drying improver is maltodextrin; among them, the maltodextrin is added according to the actual addition amount of maltodextrin in Example 3, that is, the proportional addition amount under the original composite formula, and no ultrasonic vibration is provided during the sublimation stage, and the others are the same as in Example 3: The quality indicators of the freeze-dried glucose blocks prepared in Comparative Example 4 were detected to verify whether they meet the internal control quality indicators, and the results are summarized in Table 7: Table 7 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 4
[0037] According to the experimental results in Table 7 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 4, the drying time is 23.8 h (starting from when the freeze dryer starts to evacuate the air and ending when the material is discharged).
[0038] Comparative Example 5: Based on Example 3, no composite freeze-drying improver is added, but ultrasonic vibration is provided during the sublimation stage. The ultrasonic vibration is the same as that in Example 3, and the others are all the same as in Example 3: Perform quality index detection on the freeze-dried glucose blocks prepared in Comparative Example 5 to verify whether they meet the internal control quality indicators, and the statistics are shown in Table 8: Table 8 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 5
[0039] According to the experimental results in Table 8 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 5, the drying time is 22.8 h (starting from when the freeze dryer starts to evacuate the air and ending when the material is discharged).
[0040] Comparative Example 6: Based on Example 3, the composite freeze-drying improver is: The composite freeze-drying improver is a mixture of an air-entraining agent sucrose fatty acid ester SE-15 and nanocellulose (with a diameter of 20 - 30 nm, a length of 1200 - 2600 nm, a degree of polymerization of 200 - 660, and a crystallinity of 60 - 75); among them, the mass fraction ratio of sucrose fatty acid ester SE-15 to nanocellulose is 0.65 part : 43.0 parts. And no ultrasonic vibration is provided during the sublimation stage, and the others are all the same as in Example 3: Perform quality index detection on the freeze-dried glucose blocks prepared in Comparative Example 6 to verify whether they meet the internal control quality indicators, and the statistics are shown in Table 9: Table 9 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 6
[0041] According to the experimental results in Table 9 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 6, the drying time is 15.5 h (starting from when the freeze dryer starts to evacuate the air and ending when the material is discharged).
[0042] Comparative Example 7: Based on Example 3, the composite freeze-drying improver is: The composite freeze-drying improver is a mixture of an air-entraining agent, sucrose fatty acid ester SE-15, and maltodextrin. Among them, sucrose fatty acid ester SE-15 and maltodextrin are added according to the actual addition amounts of sucrose fatty acid ester SE-15 and maltodextrin in Example 3, that is, the proportional addition amounts under the original composite formula, and ultrasonic vibration is not provided during the sublimation stage, and the others are the same as in Example 3: Perform quality index detection on the freeze-dried glucose blocks prepared in Comparative Example 7 to verify whether they meet the internal control quality indicators, and the statistics are shown in Table 10: Table 10 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 7
[0043] According to the experimental results in Table 10 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 7, the drying time is 20.2 h (starting from the time when the freeze-dryer starts to evacuate until the discharging time ends).
[0044] Comparative Example 8: Based on Example 3, the composite freeze-drying improver is: The composite freeze-drying improver is an air-entraining agent, sucrose fatty acid ester SE-15. Among them, sucrose fatty acid ester SE-15 is added according to the actual addition amount of sucrose fatty acid ester SE-15 in Example 3, that is, the proportional addition amount under the original composite formula, and ultrasonic vibration is provided during the sublimation stage, and the ultrasonic vibration is the same as in Example 3, and the others are the same as in Example 3: Perform quality index detection on the freeze-dried glucose blocks prepared in Comparative Example 8 to verify whether they meet the internal control quality indicators, and the statistics are shown in Table 11: Table 11 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 8
[0045] According to the experimental results in Table 11 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 8, the drying time is 19.0 h (starting from the time when the freeze-dryer starts to evacuate until the discharging time ends).
[0046] Comparative Example 9: Based on Example 3, the composite freeze-drying improver is: The composite freeze-drying improver is a mixture of nanocellulose (with a diameter of 20 - 30 nm, a length of 1200 - 2600 nm, a degree of polymerization of 200 - 660, and a crystallinity of 60 - 75) and maltodextrin. Among them, the mass fraction ratio of nanocellulose to maltodextrin is 40.65 parts: 3.0 parts. And ultrasonic vibration is not provided during the sublimation stage, and the others are the same as in Example 3: The quality indicators of the freeze-dried glucose blocks prepared in Comparative Example 9 were detected to verify whether they meet the internal control quality indicators, and the results are summarized in Table 12: Table 12 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 9
[0047] According to the experimental results in Table 12 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 9, the drying time is 20.4 h (starting from when the freeze-dryer starts to evacuate and ending when the material is discharged).
[0048] Comparative Example 10: Based on Example 3, the composite freeze-drying improver is: The composite freeze-drying improver is nanocellulose (with a diameter of 20 - 30 nm, a length of 1200 - 2600 nm, a degree of polymerization of 200 - 660, and a crystallinity of 60 - 75); among them, the nanocellulose is added according to the addition amount of the composite improver in Example 3, that is, the total component addition amount under the original composite formula, and ultrasonic vibration is provided during the sublimation stage, and the ultrasonic vibration is the same as that in Example 3, and the others are all the same as in Example 3: The quality indicators of the freeze-dried glucose blocks prepared in Comparative Example 10 were detected to verify whether they meet the internal control quality indicators, and the results are summarized in Table 13: Table 13 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 5
[0049] According to the experimental results in Table 13 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 10, the drying time is 19.6 h (starting from when the freeze-dryer starts to evacuate and ending when the material is discharged).
[0050] Comparative Example 11: Based on Example 3, the composite freeze-drying improver is: The composite freeze-drying improver is maltodextrin; among them, the maltodextrin is added according to the actual addition amount of maltodextrin in Example 3, that is, the proportional addition amount under the original composite formula, and ultrasonic vibration is provided during the sublimation stage, and the ultrasonic vibration is the same as that in Example 3, and the others are all the same as in Example 3: The quality indicators of the freeze-dried glucose blocks prepared in Comparative Example 11 were detected to verify whether they meet the internal control quality indicators, and the results are summarized in Table 7: Table 14 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 11
[0051] According to the experimental results in Table 14 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 11, the drying time is 22.2 h (starting from when the freeze dryer starts to evacuate and ending when the material is discharged).
[0052] Comparative Example 12: Based on Example 3, the only difference is that ultrasonic vibration is not provided during the sublimation stage, and the rest is the same as in Example 3: The quality indicators of the freeze-dried glucose blocks prepared in Comparative Example 12 were tested to verify whether they meet the internal control quality indicators and are summarized in Table 15: Table 15 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 12
[0053] According to the experimental results in Table 15 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 12, the drying time is 13.4 h (starting from when the freeze dryer starts to evacuate and ending when the material is discharged).
[0054] Comparative Example 13: Based on Example 3, the composite freeze-drying improver is: The composite freeze-drying improver is a mixture of the air-entraining agent sucrose fatty acid ester SE-15 and nanocellulose (with a diameter of 20 - 30 nm, a length of 1200 - 2600 nm, a degree of polymerization of 200 - 660, and a crystallinity of 60 - 75); among them, the mass fraction ratio of sucrose fatty acid ester SE-15 to nanocellulose is 0.65 part : 43.0 parts. Ultrasonic vibration is provided during the sublimation stage, and the ultrasonic vibration is the same as in Example 3, and the rest is the same as in Example 3: The quality indicators of the freeze-dried glucose blocks prepared in Comparative Example 13 were tested to verify whether they meet the internal control quality indicators and are summarized in Table 16: Table 16 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 13
[0055] According to the experimental results in Table 16 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 13, the drying time is 11.6 h (starting from when the freeze dryer starts to evacuate and ending when the material is discharged).
[0056] Comparative Example 14: Based on Example 3, the composite freeze-drying improver is: The composite freeze-drying improver is a mixture of an air-entraining agent, sucrose fatty acid ester SE-15, and maltodextrin; wherein, the sucrose fatty acid ester SE-15 and maltodextrin are added according to the actual addition amounts of the sucrose fatty acid ester SE-15 and maltodextrin in Example 3, that is, the proportional addition amounts under the original composite formula, and ultrasonic vibration is provided in the sublimation stage. The ultrasonic vibration is the same as that in Example 3, and the others are all the same as in Example 3: Perform quality index detection on the freeze-dried glucose blocks prepared in Comparative Example 14 to verify whether they meet the internal control quality indexes, and the results are summarized in Table 17: Table 17 Qualified indexes and actual test results of the freeze-dried glucose blocks in Comparative Example 14
[0057] According to the experimental results in Table 17 above, the internal control quality indexes can be achieved. According to the production process in Comparative Example 14, the drying time is 18.5 h (starting from when the freeze-dryer starts to evacuate and ending when discharging).
[0058] Comparative Example 15: Based on Example 3, the composite freeze-drying improver is: The composite freeze-drying improver is a mixture of nanocellulose (with a diameter of 20 - 30 nm, a length of 1200 - 2600 nm, a degree of polymerization of 200 - 660, and a crystallinity of 60 - 75) and maltodextrin; wherein, the mass fraction ratio of nanocellulose to maltodextrin is 40.65 parts : 3.0 parts. Ultrasonic vibration is provided in the sublimation stage. The ultrasonic vibration is the same as that in Example 3, and the others are all the same as in Example 3: Perform quality index detection on the freeze-dried glucose blocks prepared in Comparative Example 15 to verify whether they meet the internal control quality indexes, and the results are summarized in Table 18: Table 18 Qualified indexes and actual test results of the freeze-dried glucose blocks in Comparative Example 15
[0059] According to the experimental results in Table 18 above, the internal control quality indexes can be achieved. According to the production process in Comparative Example 15, the drying time is 19.0 h (starting from when the freeze-dryer starts to evacuate and ending when discharging).
[0060] Comparative Example 16: Based on Example 3, the only difference is that ultrasonic vibration is provided in the sublimation stage, but the ultrasonic vibration does not stop until the discharging ends, and the others are all the same as in Example 3: Perform quality index detection on the freeze-dried glucose blocks prepared in Comparative Example 16 to verify whether they meet the internal control quality indexes, and the results are summarized in Table 19: Table 19 Qualified indexes and actual test results of the freeze-dried glucose blocks in Comparative Example 16
[0061] According to the experimental results in Table 19 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 16, the drying time is 6.4 h (starting from when the freeze dryer starts to evacuate the air and ending when the material is discharged).
[0062] Comparative Example 17: Based on Example 3, the only difference is that ultrasonic vibration is provided during the sublimation stage, but the ultrasonic is only turned on when the temperature of the heating plate reaches 50°C, and the turning-on time is the same as that in Example 3, and the others are the same as those in Example 3: Perform quality index detection on the freeze-dried glucose blocks prepared in Comparative Example 17 to verify whether they meet the internal control quality indicators, and summarize them in Table 20: Table 20 Qualified indicators and actual test results of the freeze-dried glucose blocks in Comparative Example 17
[0063] According to the experimental results in Table 20 above, the internal control quality indicators can be achieved. According to the production process in Comparative Example 17, the drying time is 13.2 h (starting from when the freeze dryer starts to evacuate the air and ending when the material is discharged).
[0064] Summarize the drying times in the above Examples 1-3 and Comparative Examples 1-17 in Table 21: Table 21 Drying times in Examples 1-3 and Comparative Examples 1-17
[0065] Therefore, in summary, the present invention discloses a freeze-dried glucose block and its production process, which mainly consists of the following raw materials: glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid, and a composite freeze-drying improver. The composite freeze-drying improver is an air-entraining agent, a mixture of nanocellulose and maltodextrin; the present invention breakthroughly adopts a composite freeze-drying improver multi-component synergistic system: microbubble gas is introduced through the air-entraining agent, and the three-dimensional framework of nanocellulose and ultrasonic vibration in the early sublimation stage in the freeze-dried body synergistically guide the diffusion and escape of the microbubble gas. After the gas diffuses, a dense and through three-dimensional network pore structure with an average pore diameter of 50-100 μm is formed in the freeze-dried body; due to the special preparation raw materials of the present invention, the pore channels are unsupported and prone to collapse. Then, the glass transition of maltodextrin is inhibited to effectively maintain the structural stability of the pore channels and prevent collapse. Through the synergistic action of the air-entraining agent, nanocellulose, ultrasonic vibration, and maltodextrin, the formed dense and through three-dimensional network pore channels significantly accelerate the sublimation and overflow time of water molecules, greatly reduce the temperature during the freeze-drying process, and significantly reduce the freeze-drying time, greatly saving energy consumption. The freeze-drying preparation of the glucose block product can be realized without a high vacuum degree, improving the product qualification rate, and the production cost is greatly reduced through the composite freeze-drying improver; it has outstanding application and promotion prospects.
[0066] At this point, those skilled in the art recognize that although the embodiments of the present invention have been shown and described in detail herein, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the content disclosed in the present invention without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention should be understood and recognized as covering all these other variations or modifications.
Claims
1. A production process for freeze-dried glucose blocks, characterized in that, The production process includes the following steps: Step S1: Dissolve raw materials and introduce gas Qualified raw materials are weighed according to the formula amount. After crushing and sieving glucose, the weighed glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid, and compound freeze-drying improver are added to a blender. Start stirring and introduce gas into the mixture to obtain a glucose foaming suspension solution; the compound freeze-drying improver is dissolved in hot water and then added to the blender. Step S2: Filling and quick-freezing The glucose foaming suspension solution obtained in Step S1 is filled into a mold. The glucose foaming suspension solution filled into the mold enters a liquid nitrogen quick-freezing tunnel through a conveyor belt for quick-freezing to obtain quick-frozen glucose blocks. Step S3: Demolding and freezing The quick-frozen glucose blocks obtained in Step S2 are demolded. After demolding, they are transferred to a freeze-drying tray and quickly enter a freezing warehouse for freezing to obtain frozen glucose blocks. Step S4: Freeze-dry with ultrasonic vibration in a freeze-dryer and then discharge The frozen glucose blocks obtained in Step S3 quickly enter a freeze-dryer and are placed on the ultrasonic vibration table of the freeze-dryer. Vacuum is pumped at a low temperature. When the vacuum degree reaches the preset value, heating is started. When the temperature of the heating plate reaches 5 - 10 °C, ultrasonic vibration is started. After reaching the preset ultrasonic vibration time, ultrasonic vibration is turned off and sublimation drying continues. When the temperature of the glucose block material coincides with the preset temperature of the heating plate, the temperature is lowered and drying continues until discharging; vacuum freeze-drying is completed to obtain the freeze-dried glucose blocks; through discharging, sorting, metal detection, bagging and sealing, and after passing inspection, the finished products are warehoused. The compound freeze-drying improver is a mixture of an air-entraining agent, nanocellulose, and maltodextrin. The air-entraining agent is sucrose fatty acid ester SE-15. The nanocellulose has a diameter of 20 - 30 nm, a length of 1200 - 2600 nm, a degree of polymerization of 200 - 660, and a crystallinity of 60 - 75.
2. The production process of a freeze-dried glucose block as described in claim 1, characterized in that, In Step S1, the mass fraction ratio of glucose powder, drinking water, mango puree, banana powder, malic acid, citric acid, and compound freeze-drying improver is 42.5 - 47.5:40.5 - 45.0:6.0 - 8.5:1.0 - 2.0:0.35 - 0.50:0.2 - 0.3:3.5 - 5.5; the gas is nitrogen, carbon dioxide, or air.
3. A production process of freeze-dried glucose blocks as described in claim 1, characterized in that, In Step S1, the mass fraction ratio of the air-entraining agent sucrose fatty acid ester SE-15, nanocellulose, and maltodextrin in the compound freeze-drying improver is 0.5 - 0.75:30.0 - 50.0:2.0 - 4.
0.
4. A production process of freeze-dried glucose blocks as described in claim 1, characterized in that, In Step S1, the stirring temperature is 2 - 5 °C; the stirring speed is 600 - 1000 r / min; the stirring time is 3 - 5 min.
5. A production process of freeze-dried glucose blocks as described in claim 1, characterized in that, In Step S2, the speed of the conveyor belt entering the liquid nitrogen quick-freezing tunnel is 250 - 300 kg / h, the temperature is -50 °C, and the time to exit the tunnel is 10 - 20 min.
6. A production process of freeze-dried glucose blocks as described in claim 1, characterized in that, In Step S3, the freezing temperature is less than -35 °C, and the freezing time is greater than 8 h.
7. A production process of freeze-dried glucose blocks as described in claim 1, characterized in that, In Step S4, the vacuum degree reaches 30 - 100 Pa within 1 h; the preset temperature of the heating plate is 50 - 70 °C, and the heating rate of the heating plate is 0.7 - 5 °C / min.
8. A production process of freeze-dried glucose blocks as described in claim 1, characterized in that, In the step S4, the ultrasonic vibration frequency is 10 - 20 kHz; the ultrasonic amplitude is 10 - 20 μm; the preset ultrasonic vibration time is 20 - 40 min.
9. A production process of freeze-dried glucose blocks as described in claim 1, characterized in that, In the step S4, after the temperature of the glucose block material coincides with the preset temperature of the heating plate, the temperature is lowered, and drying is continued for 1 - 2 h before discharging. The vacuum freeze-drying time is 6 - 12 h.
10. A freeze-dried glucose block, characterized in that, The freeze-dried glucose block is prepared by the preparation method according to any one of claims 1 - 9.
Citation Information
Patent Citations
Lucid ganoderma freeze-dried quick-release tablet for enhancing immunity and preparation method thereof
CN116832001A
Complexes comprising phospholipids, water-soluble dextrin fibers and antioxidant active principles of natural origin, their preparation and use in oral formulations
EP3409293A1
Method for preparing hydrogel using high purity cellulose and cellulose powder prepared by using the hydrogel
KR1020170044434A